Cognitive Behavioral Therapy for Three Patients with Bipolar II Disorder during Depressive Episodes - Yasuhiro Kimura; Sayo Hamatani; Kazuki Matsumoto; Eiji Shimizu (Case Reports in Psychiatry)
Bipolar II disorder is a recurrent mental health disorder characterized by alternating hypomanic and depressive episodes. Providing cognitive behavioral therapy (CBT) as an adjuvant to pharmacotherapy can reduce the recurrence rate of bipolar disorder. It has not been examined whether CBT can be started during a depressive episode in patients with bipolar II disorder; however, the use of CBT during the remission period has been demonstrated to reduce recurrence. The current study is a case report involving three Japanese patients with bipolar II disorder, who started CBT during the depressive phase after a hypomanic episode was stabilized by pharmacotherapy. All patients experienced excessively positive thinking one week apart and were able to choose behaviors that would stabilize bipolar mood by observing its precursors. After intervention, patients’ bipolar mood according to the Internal State Scale (ISS) and the Beck Depression Inventory-II (BDI-II) was improved. Our findings suggested that providing CBT to patients with bipolar II disorder during depressive episodes as an adjunct to pharmacotherapy is feasible.